Severe malaria enforces short-lived effector cell differentiation but does not prevent effective secondary responses by memory CD8 T cells. - Jacob A Hildebrand; Noah R Daniels; Emma M Dehm; Benjamin D Fisher; Joseph K Guter; Chris J Janse; Erin D Lucas; Jules A Sangala; Trevor N Tankersley; Geoffrey T Hart; Sara E Hamilton (PLoS Pathogens)
Parasitic infections are a major worldwide health burden, yet most studies of CD8 T cell differentiation focus on acute viral and bacterial infections. To understand effector and memory CD8 T cell responses during erythrocytic malaria infection in mice, we utilized transgenic OT-I T cells and compared CD8 T cell responses between infection with OVA-expressing strains of Listeria monocytogenes (Lm) and Plasmodium berghei ANKA (PbA). We find that CD8 T cells expand vigorously during both infections. However, in contrast to Lm infection, PbA infection induces T cells that are heavily biased toward an IL-7Ra-deficient and KLRG1+ short-lived effector cell (SLEC) phenotype at the expense of memory precursor effector cell (MPECs) formation. PbA-induced inflammation, including IFNγ, is partially responsible for this outcome. Following treatment with antimalarial drugs and T cell contraction, PbA-primed memory T cells are rarely found in the blood and peripheral tissues but do maintain a low presence in the spleen and bone marrow. Despite these poor numbers, PbA memory T cells robustly expand upon vaccination or viral infection, control pathogen burden, and form secondary memory pools. Thus, despite PbA enforced SLEC formation and limited memory, effective secondary responses can still proceed.